Chemoselective enzymatic preparation of N-hydroxyalkylacrylamides, monomers for hydrophilic polymer matrices - Rustoy, Eduardo Miguel; Baldessari, Alicia (Journal of Molecular Catalysis B: Enzymatic)
A lipase-catalyzed procedure is described for the preparation of N-hydroxyalkylacrylamides useful among a number of electrophoretical applications such as capillary and gel electrophoresis. The N-hydroxyalkylacrylamides were prepared through an aminolysis reaction of alkanolamines on ethyl acrylate. The reaction was catalyzed by Candida antarctica lipase. The addition of radical inhibitors improved chemoselectivity and amides were obtained in high yield and purity at room temperature. Fil: Rustoy, Eduardo Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina